Analysing the challenges in implementing Vietnam’s Nationally-Determined Contribution (NDC) in the agriculture sector under the current legal, regulatory and policy environment - Trung, Nguyen Duc; Thang, Nguyen Trung; Anh, Le Hoang; Amjath-Babu, Tharayil Shereef; Sebastian, Leocadio S. (Informa UK Limited, 2020)
This study analyses the current supporting laws, regulations, strategies, national action plans, NDCs, scientific literature and other documents and policies in Vietnam to identify the barriers against the effective implementation of mitigation and adaptation agriculture activities committed in Vietnam’s NDC. It also identifies the redundancies and synergies between climate action and green growth plans of the country. As a result, the study found that there is a strong supporting legal framework for implementing NDC actions in Vietnam. However, challenges and gaps are identified in awareness and technical capacity; coordination and resource allocation; downscaling to the provinces; engagement of private sector and NGOs; regulatory framework, which are critical to NDC implementation. A set of key recommendations are proposed on how to address the challenges raised by identified barriers are developed.